1994
DOI: 10.1002/syn.890180304
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional quantification of mossy‐fiber. Presynaptic boutons in living hippocampal slices using confocal microscopy

Abstract: Confocal laser scanning microscopy (CLSM) was used to visualize presynaptic elements of mossy-fiber synapses in living rat hippocampal slices. Mossy fiber (mf) axons and their boutons were labeled in transverse hippocampal slices by injecting one of three fluorescent dyes (diI, diA, or fast diI) into stratum granulosum of the dentate gyrus and/or stratum lucidum of CA3. Three-dimensional (3D) images of the mf boutons were obtained from serial optical sections in stratum lucidum. The 3D data were used to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…1). The fluorescent band was considered to represent labelled mossy fibres, since the labelled structure had the characteristic appearance of mossy fibres (Claiborne et al 1986; Regehr & Tank, 1991; Yu & Brown, 1994) for the following reasons: first, the fluorescence was restricted to the stratum lucidum, where mossy fibres exist (Fig. 1) and, in addition, large boutons of 3‐5 μm diameter, which were located en passant along the labelled fibres, could be seen under higher magnification (× 100 objective, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1). The fluorescent band was considered to represent labelled mossy fibres, since the labelled structure had the characteristic appearance of mossy fibres (Claiborne et al 1986; Regehr & Tank, 1991; Yu & Brown, 1994) for the following reasons: first, the fluorescence was restricted to the stratum lucidum, where mossy fibres exist (Fig. 1) and, in addition, large boutons of 3‐5 μm diameter, which were located en passant along the labelled fibres, could be seen under higher magnification (× 100 objective, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have taken advantage of the combination of DiI and confocal microscopy to examine detailed physiological phenomena such as changes in axon arrangement in the retinofugal pathway of mouse embryos (Chan and Chung, 1999), mossy fiber growth in live hippocampal slices (Yu and Brown, 1994) and even mapping of complex brain circuitry . Furthermore, investigators have used confocal imaging with DiI neuronal tracing to study projections of developing CST axons, and found that more detailed tracing of DiI-labeled axons was achievable and at higher contrast compared with HRP or WGA-HRP labeling in association with light microscopy (Nagashima, 1994).…”
Section: Visualization Of the Injured Cst Using Confocal Microscopymentioning
confidence: 99%